The Use of Regenerative Medicine in the Management of Invasive Bladder Cancer. (27th August 2012) - Hyndman, Matthew E.; Kaye, Deborah; Field, Nicholas C.; Lawson, Keith A.; Smith, Norm D.; Steinberg, Gary D.; Schoenberg, Mark P.; Bivalacqua, Trinity J.
Abstract : Muscle invasive and recurrent nonmuscle invasive bladder cancers have been traditionally treated with a radical cystectomy and urinary diversion. The urinary diversion is generally accomplished through the creation of an incontinent ileal conduit, continent catheterizable reservoir, or orthotopic neobladder utilizing small or large intestine. While radical extirpation of the bladder is often successful from an oncological perspective, there is a significant morbidity associated with enteric interposition within the genitourinary tract. Therefore, there is a great opportunity to decrease the morbidity of the surgical management of bladder cancer through utilization of novel technologies for creating a urinary diversion without the use of intestine. Clinical trials using neourinary conduits (NUC) seeded with autologous smooth muscle cells are currently in progress and may represent a significant surgical advance, potentially eliminating the complications associated with the use of gastrointestinal segments in the urinary reconstruction, simplifying the surgical procedure, and greatly facilitating recovery from cystectomy.